The use of TikTok by the police - Babic, Juliana Kata Pereira (International journal of police science & management, 2025)
Police agencies continue to use social media platforms as part of their operations. Although previous research has explored the police's use of Twitter (now referred to as X), Facebook, and other platforms, no known research has explored the police's use of TikTok. As part of the present research, we conducted a content analysis of all TikTok videos posted by the Vancouver Police Department (VPD) between January 2022 and June 2023 (N = 96 videos). Our findings reveal that the VPD focused more on community-oriented content than law enforcement-oriented content in their videos. Our findings also reveal that many videos emphasized a networking strategy. Our research provides an empirical snapshot of how one police agency with a particularly popular TikTok account uses the platform. We highlight the relevance of our findings for research regarding policing and social media as well as policing practice.